(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The primary objective of the study is to manage the level of “sensitivity of salivary over serum glucose” in patients whohave been suffering from type 2 diabetes mellitus patients.Materials and Methods: There are two groups have been selected for this study for the purpose of gathering samples. In that case,Group A includes individuals below 60 years, and also their health condition was checked before the selection as a sample. In addition,Group B incorporates 60 adults after observing their diabetes levels. In that case, it can be observed that Group B has successfullycontrolled their type2 of diabetes. In order to determine the glycosylated hemoglobin and serum glucose present in the blood, the bloodsamples (“1.5ml of venous Blood”) were gathered with the help of EDTA. In this context, it is required to use a sterile container tocollect stimulated saliva from each of the groups. In this study, the “microcolumn method” has been used for the estimation of glucoseof the subjected groups. In the next phase, the result can be obtained with the help of statistical analysis with “ANOVA” and “correlationtest”.Results: In every group, the level of salivary glucose has been enhanced and also observed after doing a proper comparison. Thepresence of HbAlCc can enhance the percentage of glucose in a certain group. After doing the correlation Analysis, it can be foundthat a positive result (P<0.001) occurs between the two factors such as “salivary glucose level with HbAlc” and “serum glucose level”.Conclusion: The study has depicted that, salivary glucose can be used as a form of “noninvasive diagnostic aid”. The term diabetes hasbeen influenced by the function and composition of the salivary method.